Role of the Sterol Regulatory Element Binding Protein Pathway in Tumorigenesis - Jiang, Tao; Zhang, Guangji; Lou, Zhaohuan (Frontiers in Oncology, 2020)
Metabolic changes are a major feature of tumors. It contains various metabolic forms such as energy, lipids, and amino acid metabolism. Sterol regulatory element binding protein （SREBP）is an important module in lipid metabolism regulating and plays an important role in metabolic diseases. In recent decades, the regulatory range of SREBPs has been greatly expanded. It was found that SREBPs also played a remarkable role in tumor development. SREBPs are involved in the energy supply, lipid supply, immune environment and inflammatory environment shaping in tumor cells and as a protective umbrella for cells to support the malignant proliferation of tumor cells. Natural medicine and traditional Chinese medicine, as an important part of the drug, demonstrate multifaceted effects of SREBPs regulation and tumor inhabitation. This review summarizes the core processes involved in the involvement of SREBPs in tumors and provides a comprehensive understanding of the pathways by which natural drugs target the SREBPs pathway and regulate tumor progression.